2009
DOI: 10.1590/s0102-311x2009000100010
|View full text |Cite
|
Sign up to set email alerts
|

A serological and molecular investigation of American cutaneous leishmaniasis in dogs, three years after an outbreak in the Northwest of Paraná State, Brazil

Abstract: Classic and molecular (polymerase chain reaction - PCR) techniques were used to diagnose American cutaneous leishmaniasis in 149 dogs from an area in the northwest of Paraná State, Brazil, where an American cutaneous leishmaniasis outbreak occurred in 2002. The results were compared to a set of previously obtained results. Twenty-five dogs had positive indirect immunofluorescence (IIF) (titers > 40), including two animals with suggestive lesions. The percentage of dogs with positive IIF was similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This might be attributable to a past infection that was controlled via an immune response, as discussed elsewhere. 34 However, the possibility of false-positive results of each diagnostic test should also be considered, which might have led to the discrepancies among the diagnosing tests. For example, Mohammadiha and others reported that 3.6% (1/28) and 10.7% (3/28) of dogs from Leishmania nonendemic areas were positive by real-time PCR and ITS-based PCR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributable to a past infection that was controlled via an immune response, as discussed elsewhere. 34 However, the possibility of false-positive results of each diagnostic test should also be considered, which might have led to the discrepancies among the diagnosing tests. For example, Mohammadiha and others reported that 3.6% (1/28) and 10.7% (3/28) of dogs from Leishmania nonendemic areas were positive by real-time PCR and ITS-based PCR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider dogs to be secondary reservoirs of the parasite [12], [14], [37], playing some role in the cycle [15], [25], [26], [38], as a link between wild and domestic cycles [39] or as a risk factor for human disease [40]. Reithinger & Davies [41] report that current evidence on the role of domestic dogs as reservoir hosts for the domestic transmission of ACL is circumstantial.…”
Section: Discussionmentioning
confidence: 99%
“…For the PCR, the primers MP3H (5′-GAA CGG GGT TTC TGT ATG C-3′) and MP1L (5′-TAC TCC CCG ACA TGC CTC TG-3′) were used, which amplify a 70-bp fragment of the minicircle of the kDNA of parasites of the subgenus Leishmania (Viannia) [19] and the reaction was performed following the method described by Massunari et al [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have only isolated parasites from skin lesions (MADEIRA et al, 2005(MADEIRA et al, , 2006CASTRO et al, 2007). Moreover, Castro et al (2007) suggested that dogs are not good reservoirs for L. (V.) braziliensis and Massunari et al (2009) suggested that dogs have a secondary role in the transmission cycle of this parasite. As seen with human infection, the results from diagnostic tests on animals are discrepant, thus raising doubts regarding their validity (UCHÔA et al, 2001).…”
Section: Discussionmentioning
confidence: 99%